AUDITING NEW APPROACH OF CREDIT LOSS FOR FINANCIAL INSTITUTIONS IN THE AUDIT DATA ANALYTICS ERA: A FIELD STUDY IN EGYPT - Shaaban Ibrahim, Mohamed; Mahmoud Abdou, Rana (The journal of contemporary issues in business and government, 2022)
Purpose-The main objective of the study to propose Audit Data Analytic Tools (ADA) to develop the role of the External Auditor in enhancing the communication of the Expected Credit Loss (ECL) estimate as a very complex and subjective item of Critical Audit Matters (CAMS) of the New Audit Report. Design/methodology/approach- The study depends on uses of the field approach through a questionnaire distributed by the researcher to academic staff members of some selected universities and the audit professionals whether the internal auditors in banks listed and controlled by the Egyptian central bank & the external auditors registered in the financial regulatory authority of the big auditing firm in Egypt with expertise in the banking industry sector ( i.e Pwc, KPMG ,Grand Thorton ,EY) to test the relevance of the proposed framework for CAMS communication. Findings-The findings of the study show the significant importance of ECL i.e.,CAMS Communication to the financial statement users as it promotes the user to the audit report and finally improves the understanding and relevance of the related financial statements. Thus,When the CAMS disclosures in the audit report are provide, investors may be more confident that the auditors have determined and appropriately addressed the most highly risky assertions in the financial statements which reflect on the audit quality. Originality/value-This study contributes to the audit literature by proposing a suitable Audit Data analytics tool (tools) to develop an independent estimate (i.e. Point of estimate) for the new ECL as a very complex and subjective CAMS item in order to stand on its reasonableness by the external auditor. As well as proposing the relevant form for communicating such information as a CAMS in the 1 audit report.